Evaluation of the XRecorder Application via Video on Learning Al-Islam and Muhammadiyah in the Middle of the Covid-19 Pandemic - Mohd. Neulborne; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2020)
The purpose of the research is to evaluate E-learning in Al-Islam and Muhammadiyah 1 academic year 2020/2021 courses, where the website application provides learning data and information that can be accessed by students or students, without having to face the teacher. E-learning forms of Al-Islam and Muhammadiyah learning through XRecorder on WhatsApp at the Muhammadiyah University of Enrekang. Learning Al-Islam and Kemuhammadiyahan uses an Online learning system (E-learning) that is centralized and integrated into an information system based on the Moodle LMS (Learning Management System) website, to help students studying at the University of Muhammadiyah Enrekang in the lecture process and make it easier to get material and information related to Al-Islam and Muhammadiyah courses, in making the XRecoreder system on WhatsApp. The research method collects data and information about lecture materials as well as students and lecturers from the recorder via WA and the You Tube link. The results of the learning evaluation research found that XRecorder on WhatsApp supports the E-learning learning process, so it can be concluded that with the XRecorder application via Video it can make it easier for students to access information and lecture materials and lecturers in carrying out the lecture process at Muhammadiyah of Enrekang University.